The prevalence of HBV, HCV, and HIV among hemodialysis patients in a tertiary care hospital in Mashhad, Iran - Khorrami, Mohammad-Bagher; Amali, Arian; Sadeghi, Mahmood; Riahi-Zanjani, Bamdad (The Journal of Infection in Developing Countries, 2023)
Introduction: Hepatitis and acquired immunodeficiency are major health concerns in high-risk patients with renal failure undergoing hemodialysis. This might be due to the number of blood transfusions, age, and dialysis duration. We aimed to investigate the prevalence of HBV, HCV, and HIV in hemodialysis patients to determine the effectiveness of preventive measures already in place and the possible correlation between various risk factors and viral infection in the Hemodialysis Center in Mashhad, Iran. Methodology: Sixty-five patients were included in a retrospective cross-sectional study. The demographic information was collected. Hepatitis-B surface antigens, anti-HCV, and anti-HIV antibodies were screened using ELISA. Results: Out of 65 patients, 34 (52.3%) were male, and 31 (47.7%) were female. Mean duration of dialysis was 30.68 ± 26.39 months, and the mean age was 64.95 ± 14.09 years. We found 9 (13.8%) patients that were HBV positive (HbsAg-positive), and 3 (4.6%) patients were HCV positive. Sex and the number of blood transfusions were found to be risk factors for HBV infection and had statistical significance (p = 0.02 and p = 0.01, respectively). No statistical significance was found between HBV- and HCV- positivity and the mean age of patients (p = 0.84 and p = 0.76, respectively). All patients were HIV-negative. Conclusions: Prevalence of HBV was high and significant. More preventive measures need to be developed, and further studies should be conducted to examine the effectiveness of these measures. Moreover, evaluating the prevalence rates of HBV, HCV, and HIV in other hospitals and dialysis centers in Mashhad is recommended to minimize viral infections. Initial HBV vaccination for patients that require hemodialysis is crucial.